Solar power Pump Farmer Technology Ellak Daya Village Farmers with modern rural agricultural irrigation supported by a smart hybrid inverter system in the Lenteng sub-district, Sumenep, Indonesia - Cahyati, Cholilul; Suwandi, Ahmad; Santosa, Ribut; Setiawan, Muhammad Ikhsan; Prawito, Adi; Sukoco, Agus (LPPM of NAROTAMA UNIVERSITY, 2023)
Ellak Daya Village is one of the villages in Lenteng sub-district, Sumenep Regency with dry land/fields 63.3% of the total land with commodity crops of Corn, Beans, Soybeans, Rice and herbal chilies, which are only capable of maximum production in rainy season during the dry season the fields/dry land in Ellak Daya are less productive. This condition is one of the triggers for Ellak Village to be a village with the potential for extreme poverty, based on an analysis of the identified problems, namely: Problems in the field of management. Arranging planting patterns and irrigation schedule systems, in the processing sector, namely the absence of effective and cheap irrigation facilities and the absence of irrigation methods. The aim of training and mentoring is carried out so that farmer groups have the skills to regulate planting patterns, have management skills in irrigation schedules, apply technology. solar cell pump with energy sources from nature. Activities that have been carried out in the form of training and mentoring are: FGD, socialization, training and mentoring which will be carried out from 26 September to 20 November 2023 at the village hall and at the farmer group's house. The problems in this activity are: the partner's age is 50 years and over, and their education level is still low. Achievement of targets in training and mentoring in this program is measured by giving a Pre Test and Post test. Conduct training. 100% of participants know about the procedures for planting patterns and 40% understand how to set planting patterns, participants who attend training and mentoring activities on average above 65% of the total number of members